The Year of Living Dangerously: Sarajevo '92
The interviewer first talks through an interpreter with a physician about what kind of illnesses he is treating and his opinion about the war. Then a mother with her two children is interviewed about how they were able to leave Sarajevo, will they go back and their general opinions about the war.